The social policies of emerging economies: Growth and welfare in China and India - Arjan de Haan (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
Social policies play a critical role in the transformation of emerging economies. This paper discusses this with reference to China and India, with their very distinctive public policy approaches. Much of the economics literature either does not pay much attention to social policy or regards it as secondary at best or as a market enemy at worst. Views on social policy in emerging economies see this as either lagging or threatening growth. Instead, this paper argues, social policy is congruent and constitutive, and sustainable social policies are those that are formulated as part of economic policies and transformation, and, in turn, shape the conditions of enhancing markets and productivity. The paper describes how the 'great transformation' of both countries shapes social policy responses, the institutions and ideas that give very different shapes to the two countries' policies and the way policies vis-à-vis minorities are situated in both countries' social policies. The conclusion argues for the distinct research agenda that follows from this conceptualisation of social policy.
Keywords: 330; social policy; cash transfers; emerging economies; China; India; Sozialpolitik; Öffentliche Sozialleistungen; Schwellenländer; China; Indien